A nation among nations : America's place in world history - Bender, Thomas, 1944- 1944- (Hill and Wang, 2006)
Contends that American history must be placed in a global context, explaining that the obstacles being faced by the United States have been overcome in the past by other countries whose examples can impart powerful lessons.